2021
DOI: 10.7759/cureus.13349
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Sarcomas: A Retrospective Analysis of a Cohort of 62 Patients

Abstract: Background and objective Uterine sarcomas are rare tumors, and they account for 4% of all uterine malignancies. These tumors are characterized by a great diversity of histological types, and current knowledge regarding their treatment is limited. The aim of our study was to analyze a cohort of patients with uterine sarcomas with respect to the histological types of their tumors, as well as their prognosis and treatment. Materials and methods This was a retrospective analysis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 15 publications
4
8
0
Order By: Relevance
“…In our study, CSs represented 45.3% of cases, followed by LMSs, which constituted 31.7%. Taking into account other published studies that included CSs, despite the change in FIGO staging, the results herein are similar to those of Eiriz et al, 44% [11], and other studies [12], lower than that reported by Sait et al, 58% [9], and higher than that reported by Gao Y. et al, 23% [3]. We do not know the substantial basis for these differences, but they may be due to differences in the mean age of the patients treated by each centre.…”
Section: Observational Studysupporting
confidence: 89%
See 3 more Smart Citations
“…In our study, CSs represented 45.3% of cases, followed by LMSs, which constituted 31.7%. Taking into account other published studies that included CSs, despite the change in FIGO staging, the results herein are similar to those of Eiriz et al, 44% [11], and other studies [12], lower than that reported by Sait et al, 58% [9], and higher than that reported by Gao Y. et al, 23% [3]. We do not know the substantial basis for these differences, but they may be due to differences in the mean age of the patients treated by each centre.…”
Section: Observational Studysupporting
confidence: 89%
“…Again, taking into account the entire series and focusing on clinical variables, particularly age, herein, the mean age at diagnosis was 59.5 years, very similar to other studies [4,5,[8][9][10][11]. Among the subgroups, there were significant differences, highlighting 4 years earlier in the ESS group and 3 years later in the CS and other sarcoma groups (p < 0.001).…”
Section: Observational Studysupporting
confidence: 86%
See 2 more Smart Citations
“…As most patients are asymptomatic at the time of diagnosis, therefore, they usually have poor prognosis. The heterogeneous of UCS is the critical factor for the different treatment response and prognosis [ 4 ]. However, there is an urgent need to explore molecular mechanisms and identify of novel biomarkers in the treatment and prognosis of UCS.…”
Section: Introductionmentioning
confidence: 99%